Anti-inflammatory activity of leaves extracts of murraya koenigii l. - ABHISHEK MATHUR; GBKS PRASAD; V.K DUA (International Journal of Pharma and Bio Sciences, 2011)
This work has been done for the investigation of the anti-inflammatory activity of solvent extracts of dried leaves of Murraya koenigii Linn. by oral administration at dose of 100, 200 and 400 mg/kg body weight in healthy albino rats. Extracts were studied for its anti-inflammatory activity by using carrageenan- induced hind paw edema in albino rats and the mean increase in paw volume and % inhibition in paw volume were measured plethysmometrically at different time intervals after carrageenan (1% w/v) injection. The methanol extract showed significant (P < 0.001) reduction in the carrageenan-induced paw edema in comparison to aqueous extracts. Petroleum ether and hexane extracts showed no reduction in paw edema. The methanol extract showed anti-inflammatory effect in dose dependent manner when compared with the control and standard drug, Aspirin (10mg/kg, p.o). These inhibitions were statistically significant (p < 0.05). Thus our investigation suggests a potential benefit of methanol and aqueous extracts of leaves of Murraya koenigii in treating conditions associated with inflammation. This study illustrates about the presence of some active polar compounds in the leaves extracts which might be responsible for anti-inflammatory activity.